The Road to Calvary: Tracing the Diachronic Instability in Representations of the Cleric in Modern Irish Film - Martin, Jacob Dennis (Trinity College Dublin. School of Creative Arts. Discipline of Drama, 2023)
This thesis argues for the diachronic contingency of the priest in modern Irish cinema. This study utilises Richard Kearney?s account of `incarnate? and `excarnate? subjectivity to construct an analogous model for analysing the placement of the priest in Irish film over the past four decades. This study uses the socio-historical horizon of post-Independence Ireland as a critical lens to evaluate the chronological shift of the characterization of the priest in Irish film from `incarnate? subject in the decades of the 1970s and 1980s, to `excarnate? disembodied signifier of the institutional Catholic Church during the Celtic Tiger era. Finally, the study concludes by presenting an account of the renewed `incarnate? priestly characterization emerging from Ireland's cultural and societal landscape, post-economic collapse. This study will provide a close reading of several key cinematic texts from each of the periods. It will analyse the clerical representation in these cinematic texts concerning themes and discourses surrounding the priest concerning space, mandatory clerical celibacy, cultural nationalism, masculinity, and the non-maternal female. To assist in this analysis, this study articulates a clerical typology established in Hollywood from the Depression to the beginning of the Cold War, wherein the `Irish? priest served as a model of urban immigrant assimilation into mainstream American society. The two primary cinematic archetypes of priest that emerged during this period, the `social worker? priest and the `mayor? priest, also represented a shift in prevailing notions of manliness in the United States, moving away from the violent underworld figure as manifested in the gangster film, and toward the benevolent, institutional authority figure leading up to the Second World War. This thesis will then examine how these clerical archetypes of the `Irish? priest were repurposed and frequently subverted by modern Irish filmmakers as a means of subverting received images of the Irish and Ireland promulgated by American and British cinemas in the time before the rise of an indigenous cinema emerged in the 1970s. Due to the Catholic Church?s historical influence, the priest in the Irish cinematic context is invariably affixed to discourses surrounding authority, not faith and spirituality, as found in clerical depictions in other national cinemas. Thus, the primary concern of this thesis is evaluating the cinematic cleric in relationship to the Catholic Church?s decline in authority and influence due to the modernising project in the Irish Republic and the revelations of clerical abuse that emerged toward the end of the twentieth century.
APPROVED
Keywords: Film Studies; Irish Film; Clerical Representations; Irish National Cinema; Catholic Church in Ireland; Hollywood's Golden Age; Clerical Abuse Crisis; John Ford; The Quiet Man; Irish Studies; Richard Kearney; Ex-carnate; Anatheism; Vatican II; Classic Hollywood; Bob Quinn; Clerical Celibacy